Republic Steel's Operations at Port Henry, Mineville, and Fisher Hill - Linney; Robert J. (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1943)
REPUBLIC Steel Corporation's iron-ore properties in the Adirondacks consist of mines, mills, and sintering plants in the Mineville and Port Henry area and at Lyon Mountain. This article will deal with the properties in the vicinity of Mineville and Port Henry. In 1938, when Republic leased the Mineville- Port Henry operations from the Witherbee Sherman Corp., these properties had just come through some hard depression years. As a result, the mine development program was far behind schedule; most of the equipment needed replacement; and above all, the entire system of mining had to be completely changed to reduce operating costs. The concentrator had been in operation for many years; the process was dry and dusty. Machinery and equipment were either badly worn or entirely obsolete. The sintering plant, also long in operation, was badly in need of repairs.